Feminisme Radikal dalam Novel Kenanga Karya Oka Rusmini - Milvina Dahliah; Yayah Chanafiah; Emi Agustina (UNIB Press, 2026)
This study aims to determine the representation of radical feminism and the form of women's resistance against the patrilineal system in Bali in the novel Kenanga by Oka Rusmini. This research uses radical feminist theory and utilizes Schleiermacher's hermeneutic analysis technique. The data source for this research is the novel Kenanga by Oka Rusmini. The technique used is the library study technique. Description of the structure of the novel Kenanga as a means of initial understanding in dissecting the novel through radical feminism. The results of the study show that there is a representation of radical feminism in the novel Kenanga by Oka Rusmini which negates and affirms the patrilineal system in Bali through women's physiology, sexual politics, and mothering. The form of negation of female figures towards the patrilineal system in Bali is 1) Kenanga's attempt to seize autonomy over her body, mind, and decisions, 2) Dayu Ratna through her actions, namely leaving home and becoming single, 3) Mrs. Susila chose to nyerot, and 4) Intan through her actions adopted the Kenanga ideology. Based on the research that has been conducted on the novel Kenanga, it was found that the author's efforts in depicting the patrilineal system of Balinese society can be an opportunity and give rise to a series of oppressions against women. Keywords: radical feminism, bali patrilineal system.